Wireless breathing system for long term tele-monitoring of respiratory activity - Reshma P, P Ponni ,Alex rozario (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Monitoring breathing signal application “Breath Taking” reliably detect variation human in the human breathing rate. Monitoring breathing may have application in detecting the sudden infant death syndrome (SIDS), which is the largest cause of death in infants. Breath taking non-invasively detects the variations. The application does not provide a direct measure of breathing. Our project is a working model which incorporates sensors to measure parameters like body temperature, heart beat rate, respiratory rate and ECG. A micro-controller board is used for analyzing the inputs from the patient and any abnormality felt by the patient causes the monitoring system to give an alarm. Also all the process parameters within an interval selectable by the user are recorded online. This is very useful for future analysis and review of patient’s health condition. For more versatile medical applications, this project can be improvised, by incorporating blood pressure monitoring systems, dental sensors and annunciation systems, thereby making it useful in hospitals as a very efficient and dedicated patient care system